2012
DOI: 10.1016/j.radonc.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dose heterogeneity on late normal tissue complication risk after hypofractionated whole breast radiotherapy

Abstract: a b s t r a c tBackground and purpose: Linear quadratic models predict that hypofractionation increases the biological effect of physical dose inhomogeneity. The clinical significance of this effect was tested retrospectively in a trial of adjuvant breast hypofractionation. Methods: The UK FAST trial randomised 915 women after breast conservation surgery between standard fractionation and two dose levels of a 5-fraction regimen delivering 5.7 or 6.0 Gy fractions in 5 weeks, using 3D dosimetry. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…who demonstrated that larger volume receiving >53.9 Gy was a significant predictor of radiation induced skin toxicity [40]. The recent UK FAST trial reported that, after adjusting for breast size and surgical deficits, there was no evidence that the risk of late adverse effects of HF-WBI was associated with dose inhomogeneity [41]. Conversely, our results suggest that dose inhomogeneities (V > 104% and V > 107%) have a significant impact on the occurrence of severe subcutaneous late reaction (p = 0.00864 and p = 0.02045, respectively) but we did not find any correlation between dosimetric parameters and both acute and late skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…who demonstrated that larger volume receiving >53.9 Gy was a significant predictor of radiation induced skin toxicity [40]. The recent UK FAST trial reported that, after adjusting for breast size and surgical deficits, there was no evidence that the risk of late adverse effects of HF-WBI was associated with dose inhomogeneity [41]. Conversely, our results suggest that dose inhomogeneities (V > 104% and V > 107%) have a significant impact on the occurrence of severe subcutaneous late reaction (p = 0.00864 and p = 0.02045, respectively) but we did not find any correlation between dosimetric parameters and both acute and late skin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Deantonio et al 30 on a hypofractionated whole-breast study (45 Gy in 20 fractions, 2.25 Gy/fr and 9 Gy boost) reported that breast volume increased the hazard of late toxicity over time (hazard ratio =1.27, 95% CI =1.04–1.55, and P =0.016) when analyzed with Cox’s proportional hazards regression model. Despite these discrepancies, Tsang et al 31 in a report on hypofractionated UK FAST trials showed that the dose heterogeneity does not impact on the risk of 2-year change photographic breast appearance after hypofractionation so in the START A and B Trial large breast volume is not considered an exclusion criterion for hypofractionation because the lower limit of the α/β ratio for adverse effects regarding breast appearance was 2.0 Gy. 31 Anyway, a modern technique such as intensity-modulated radiation therapy seems to solve overdoses in large breasts as reported by Hannan et al 32 In our study, there was no significant correlation between BD (as surrogate of dose heterogeneity) with late toxicity and cosmesis although a PTVbr over 1,300 cc significantly correlated with greater toxicity as seen in the univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these discrepancies, Tsang et al 31 in a report on hypofractionated UK FAST trials showed that the dose heterogeneity does not impact on the risk of 2-year change photographic breast appearance after hypofractionation so in the START A and B Trial large breast volume is not considered an exclusion criterion for hypofractionation because the lower limit of the α/β ratio for adverse effects regarding breast appearance was 2.0 Gy. 31 Anyway, a modern technique such as intensity-modulated radiation therapy seems to solve overdoses in large breasts as reported by Hannan et al 32 In our study, there was no significant correlation between BD (as surrogate of dose heterogeneity) with late toxicity and cosmesis although a PTVbr over 1,300 cc significantly correlated with greater toxicity as seen in the univariate and multivariate analyses. In regard to the role of adjuvant chemotherapy in breast cancer, the DBCG-82TM protocol 33 and a multivariate analysis by Recht 34 have reported a negative impact of chemotherapy on cosmetic outcome and late normal tissue reactions after standard whole-breast radiotherapy but no many data are available with hypofractionation trials.…”
Section: Discussionmentioning
confidence: 99%
“…• cosmesis in breast cancer (FAST trial) 111 • proctoscopy at 1 year for rectal toxicity post radiotherapy for prostate cancer 112 The individual risk of non-malignant tissue toxicity to radiotherapy treatment can be assessed using markers such as serum TGF-β1 levels as a surrogate of fibrosis in breast cancer 113 and pneumonitis in lung cancer 114 . F-FDG-PET • Low post-treatment SUV associated with better overall survival in a meta-analysis (using trial-specified cut-off values) 154 • Decrease in SUV max of ≥50% from baseline to week 1 or 2 (10 or 20 Gy) of CRT was associated with higher 2-year OS 155 Examples of some clinical parameters are provided, as they might represent useful primary or secondary end points for certain patient subgroups or for important areas of clinical need (for example, likelihood of accelerated approval by regulatory agencies).…”
Section: Box 6 | Non-malignant Tissue Toxicitymentioning
confidence: 99%